Schisandrin B down‐regulated lncRNA BCYRN1 expression of airway smooth muscle cells by improving miR‐150 expression to inhibit the proliferation and migration of ASMC in asthmatic rats - Zhang, Xiao‐yu (Cell Prolif, 2017)
OBJECTIVE: The mechanism of Schisandrin B on the proliferation and migration of airway smooth muscle cells (ASMCs) in asthmatic rats was explored. METHODS: SD rats were divided into three groups: control (group 1), model (group 2) and model + Schisandrin B (group 3). miR‐150 and lncRNA BCYRN1 levels were measured by qRT‐PCR. The combination of BCYRN1 and miR‐150 was detected by RNA pull down. ASMCs’ viability/proliferation/migration were examined by WST‐1 assay and 24‐well Transwell system. RESULTS: Schisandrin B up‐regulated miR‐150 expression and down‐regulated BCYRN1 expression in sensitized rats. Schisandrin B reversed the expression of miR‐150 and BCYRN1 in MV‐treated ASMCs. In addition, Schisandrin B inhibited the viability, proliferation and migration of MV‐induced ASMCs. We also found miR‐150 inhibited BCYRN1 expression which was proved by experiments using ASMCs transfected with miR‐150 inhibitor. CONCLUSION: Schisandrin B increased miR‐150 expression and decreased BCYRN1, and BCYRN1 expression was inhibited by miR‐150, which indicated that Schisandrin B could regulate BCYRN1 through miR‐150.